Tef Eragrostis tef (Zucc.) Trotter - Ketema, S.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
Tef is an important, traditional cereal crop in Ethiopia that grows well under various stress conditions and is extensively used in Ethiopia but is little known elsewhere. This book considers the conservation and genetic resources of tef, and reviews various aspects of its taxonomy, origins and centre of diversity, properties and uses, characterization and evaluation, breeding, production, ecology, agronomy, and limitations, prospects and research needs. Two appendices are supplied listing: (1) research workers and institutes undertaking research; and (2) centres maintaining collections of tef. (Abstract © CAB ABSTRACTS, CAB International)